Developing knowledge asset valuation model using knowledge experts - Wong, Man Wai; Ramasamy, Ammuthavali; Othman, Marini (2016)
Knowledge assets which relate to an organization's core business can ensure its competitive edge in business competition by transforming knowledge into goods and services. However unlike physical asset, Knowledge Asset is intangible and there are inadequate techniques to measure the Knowledge Asset. The value of the Knowledge Assets varies, depending on human cognition and awareness which includes context sensing, personal memory and cognitive processes. The aim of this research is to interpret the value of the Knowledge Asset into a meaningful and tangible way.The objective is to develop a model that defines the value of Knowledge Assets.The research approach used is a qualitative single case research. The research has begun with a literature review, document study and interview for information gathering. The findings from the literature review reveals existing framework or model which applied to measure intangible asset.Whereas the document study reveals the factors that triggered event to create,review, update and dispose the Knowledge Asset.This information is used as a foundation to develop the conceptual model. Interviews were conducted and the model presented to the Knowledge Management manager and Knowledge Engineers to collect feedbacks about the conceptual model. As the result, the proposed model enables the Manager and Knowledge Engineers to use the identified factors to value the Knowledge Assets easily and interpret its value into more meaningful and tangible way.